Formação universitária de professores para o ensino da linguagem escrita: um estudo a partir dos discursos didático-formadores - Costalonga, Elida Maria Fiorot (2006)
The study aimed at analyzing the theoretical-methodological treatment given to the teaching of Written Language in a process of education teachers-literacy teachers , taking into account the nature of that professional role in the triad didactic: teacher/ student/ object- writing. The initial idea was that the knowledge of writing is enrolled in the story of discursive actions of human- in- the- world- with- Another. As reference there is a theoretical-conceptual methodology inspired in Vygotski (1993, 1995), Bakhtin (1995, 2003), Foucault (2002) and Eco (1989, 1995), as well, studies in the Language field, in which the ones from Faundez and Mugrabi (2000, 2003) stand out, facing the theoretical tools that present and that seem adequate to the object and to the goals of that work. The study field was PEC- Municipal University Education, developed under the coordination of PUC-SP, which goal was to offer Licentiate for teachers specialized in teaching children and beginning grades of the Fundamental Teaching of municipal schools. This Program uses a non conventional methodology using advanced technology, printing material and diversified team of teachers. Considering that, the teaching content is transmitted by determined discursive ways from didactic utterance destined for students-teachers, there is an analysis of conceptions and subjacent feelings to foreseen activities in order to orienting about their role in the initiation process of the children in the world of written language. In general, what the didactic utterance, in the study ambit, provide is a group of data that project a triadic configuration in which the interrelation formers/student-teachers/ writing teaching seem lacunaria and inconsistent. That inconsistence observed in the university formation tends to affect the interrelations teacher/children/object-written, for the emphasis in the formatting discourses in making the teachers believe that the psychogenetic theory of the written language is the only theory that make them able to do adequate interventions, not considering multiple accomplishments and multidimensionality of the written language development process by children. The evidence found lead to conclude that, in spite of the innovation attempts, there are more continuities than ruptures in relation to conceptions and criticized practices